Evaluation of portable Raman spectroscopy and handheld X-ray fluorescence analysis (hXRF) for the direct analysis of glyptics - Lauwers, D (2017)
In archaeometry, the advantages of a combined use of Raman spectroscopy and X-ray fluorescence spectroscopy are extensively discussed for applications such as the analysis of paintings, manuscripts, pottery, etc. Here, we demonstrate for the first time the advantage of using both techniques for analysing glyptics. These engraved gemstones or glass materials were originally used as stamps, to identify the owner, for instance on letters, but also on wine vessels. For this research, a set of 64 glyptics (42 Roman glass specimens and 22 modern ones), belonging to the collection of the museum ‘Quinta das Cruzes’ in Funchal (Madeira, Portugal), was analysed with portable Raman spectroscopy and handheld X-ray fluorescence (hXRF). These techniques were also used to confirm the gemological identification of these precious objects and can give extra information about the glass composition. Raman spectroscopy identifies themolecular composition as well as on the crystalline phases present. On the other hand, hXRF results show that the antique Roman glass samples are characterisedwith low Pb and Sn levels and that the modern specimens can be discriminated in two groups: lead-based and non-lead-based ones.